El piso duro como espacio social de lo cotidiano. Intervenciones en el polígono urbano del cantón Píllaro. - Sánchez Arellano Esteban Mateo (2024)
The relevance of developing this project with the theme of "The hard floor as a social space of everyday life. Interventions in the urban area of the Píllaro canton" is based on its potential to significantly optimize the functionality, accessibility, sustainability and dynamism of urban public spaces. Through carefully planned interventions, these spaces can improve people's daily quality of life and promote a more compact, inclusive and resilient city. Píllaro, identified as an intermediate city due to its unique characteristics and qualities, is a canton that has shown constant expansion towards its peripheries over time, bringing with it a number of problems. This growth has been driven by multiple factors, such as scarcity of public space, population growth, urbanization and economic development. This represents a process of urban transformation that presents challenges and opportunities for the planning and management of the territory. It is proposed to use the AEUB methodology to examine and analyze the current situation of the Píllaro canton in terms of urban sustainability, indicators are applied that allow a quantitative analysis of the specific problems facing the canton, in order to implement specific and measurable strategies. Therefore, it is proposed to develop interventions in public space through the creation of a network of squares, with the purpose of addressing the various problems identified. This initiative, supported by the analysis prior to being carried out, will allow a coherent and aligned process to be carried out. with the specific needs of the community. The implementation of the network of squares seeks to prevent the canton from continuing to expand by improving the quality of urban life, promoting social interaction, increasing the availability of public spaces, and strengthening local identity.